PROBLEMATIKA PROGRAM TAHSIN DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN MAHASISWA DI IAIN CURUP - Nurjannah Taklim; Suaidah Sri Dewi; Deli Deli; Fitriyani Fitriyani; Intan Priska (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This research aims to find out what problems students have in the tahsin program and what efforts students make to improve their ability to read the Al-Qur'an. This type of research is qualitative with a descriptive approach. Data type: observation and interviews and data sources are students and teachers. The stages of data analysis techniques are: data reduction, data presentation, and drawing conclusions. Stages of data wetness: source triangulation and data triangulation.The results of the research show that (1) The problems of IAIN Curup's 2nd semester Islamic religious education study program students in reading the Qur'an originate from several factors, namely the Al-Qur'an reading factor, the time factor and the lack of student seriousness and interest. (2) Students' efforts to improve their ability to read the Al-Qur'an are to increase interest and enthusiasm in reading the Al-Quran and give them time to study again at home. Meanwhile, the teacher's efforts are made by providing value that is equivalent to the student's effort in memorizing and always motivating students that reading is not only to achieve grades in lectures but also to get rewards from Allah SWT.